Role of Vesicular Glutamate Transporter 3 and Optineurin In Metabotropic Glutamate Receptor 5 Signaling - Ibrahim, Karim (Université d'Ottawa / University of Ottawa, 2023)
Metabotropic glutamate receptor 5 (mGluR5) is a key regulator of numerous brain functions including memory, cognition, and motor behavior. Dysregulation of mGluR5 signaling is evident in Huntington's disease (HD) neuropathology, an inherited, neurodegenerative disease characterized with progressive deterioration in motor, cognitive, and psychiatric functions. In this context, two cellular proteins draw particular interest for this thesis: vesicular glutamate transporter 3 (VGLUT3) and optineurin (OPTN). VGLUT3 modulates glutamate release from selected neurons that are affected by HD, while OPTN is a mGluR5-interacting protein and contributes to neuronal vulnerability in HD. However, current evidence on their involvement in mGluR5 signaling and HD pathogenesis is still lacking. Using VGLUT3 knockout (VGLUT3⁻ᐟ⁻) mice, we showed that this transporter dynamically regulated glutamate receptor densities in different brain regions. Of note, VGLUT3 deletion upregulated mGluR5 in the cerebral cortex and the striatum, unlike the hippocampus which exhibited reduced mGluR5 cell surface densities. We then crossed VGLUT3⁻ᐟ⁻ mice with the zQ175 knock-in mouse model of HD (zQ175:VGLUT3⁻ᐟ⁻) to assess the impact of VGLUT3 transmission loss on HD progression. The longitudinal behavioral assessment revealed that VGLUT3 ablation rescued the deficits in motor coordination and short-term memory in both male and female zQ175 mice throughout 15 months of age. Furthermore, VGLUT3 deletion rescued striatal cell loss likely via activation of Akt and ERK1/2 cellular pathways, with no impact on total mutant huntingtin aggregation or the associated microgliosis. To delineate the role of OPTN in mGluR5 signaling, we employed a CRISPR/Cas9 OPTN-deficient cell line and global OPTN knockout mice. We demonstrated that OPTN was essential for mGluR5-mediated canonical signaling and ERK1/2 activation in both the striatal cell line, STHdh^Q7/Q7, and acute hippocampal slices. We then showed that OPTN deletion impaired autophagic machinery via GSK3β/ZBTB16 and mTOR/ULK1 signaling pathways downstream of mGluR5. This work offers novel insights into the molecular roles of VGLUT3 transmission and OPTN in mGluR5 signaling and provides a rationale for their targeting to therapeutically mitigate pathological mGluR5 signaling in HD.
Keywords: mGluR5; VGLUT3; Optineurin; Huntington's disease; Neurodegeneration; GPCR; Glutamate